2018
DOI: 10.1371/journal.pone.0199080
|View full text |Cite
|
Sign up to set email alerts
|

Non-nutritive sweeteners possess a bacteriostatic effect and alter gut microbiota in mice

Abstract: Non-nutritive sweeteners (NNSs) are widely used in various food products and soft drinks. There is growing evidence that NNSs contribute to metabolic dysfunction and can affect body weight, glucose tolerance, appetite, and taste sensitivity. Several NNSs have also been shown to have major impacts on bacterial growth both in vitro and in vivo. Here we studied the effects of various NNSs on the growth of the intestinal bacterium, E. coli, as well as the gut bacterial phyla Bacteroidetes and Firmicutes, the balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 44 publications
12
93
0
9
Order By: Relevance
“…In a recent study, Wang et al [2018] reported a strong inhibitory effect of ace-K, saccharin, and sucralose at high concentrations (12.5 and 25 mg/mL) on E. coli. Here, we also studied the effects of ace-K and aspartame on E. coli growth per se.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In a recent study, Wang et al [2018] reported a strong inhibitory effect of ace-K, saccharin, and sucralose at high concentrations (12.5 and 25 mg/mL) on E. coli. Here, we also studied the effects of ace-K and aspartame on E. coli growth per se.…”
Section: Resultsmentioning
confidence: 96%
“…Some studies in recent years have reported that artificial sweeteners, including aspartame, change the composition of gut microbiota and induce glucose intolerance [Bokulich and Blaser, 2014;Palmnäs et al, 2014;Suez et al, 2014Suez et al, , 2015. Acesulfame potassium (ace-K) is another widely used NAS [Wang et al, 2018]. ace-K has been shown to induce weight gain as well as alter the gut microbiota profile in mice [Bian et al, 2017].…”
Section: Introductionmentioning
confidence: 99%
“…Such deleterious effect was prevented when mice were treated with broad-spectrum antibiotics against Gram-negative or Gram-positive bacteria. The fact that sucralose displays bacteriostatic action on several gut microbes (5,6) , and that most of the sucralose is not absorbed in the intestine (1,7,8) , gives support to observations showing that sucralose can alter gut microbiome composition (6,9) . Taken together, the notion that sucralose influences glucose control through alterations in intestinal microbiota has emerged.…”
mentioning
confidence: 80%
“…Recently the gut microbiome has emerged as a factor that could contribute to the biological effects of NAS, in particular sucralose (31) . Early environmental studies revealed a strong bacteriostatic effect of several NAS, including sucralose and saccharine (5,6,31,32) . Wang et al (6) also showed increases in Firmicutes in mice exposed to sucralose.…”
Section: Evidence Of Metabolic Impairments For Non-energy Artificialmentioning
confidence: 99%
See 1 more Smart Citation